2010
DOI: 10.3892/ijo_00000790
|View full text |Cite
|
Sign up to set email alerts
|

Vascular infarction by subcutaneous application of tissue factor targeted to tumor vessels with NGR-peptides: Activity and toxicity profile

Abstract: Abstract. tTF-NGR consists of the extracellular domain of the (truncated) tissue factor (tTF), a central molecule for coagulation in vivo, and the peptide GNGRAHA (NGR), a ligand of the surface protein aminopeptidase N (CD13). After deamidation of the NGR-peptide moiety, the fusion protein is also a ligand for integrin · v ß 3 (CD51/CD61). Both surface proteins are upregulated on endothelial cells of tumor vessels. tTF-NGR showed binding to specific binding sites on endothelial cells in vitro as shown by flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In 1998, stimulated by P. Thorpe’s work [ 28 ], our laboratory started to design a group of new bifunctional tTF fusion proteins to target procoagulatory activity selectively into the tumor vasculature and to induce tumor infarction [ 48 , 51 , 63 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Re-targeting Tf To Tumors—non-clinical Results and Translation Into The Clinicmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1998, stimulated by P. Thorpe’s work [ 28 ], our laboratory started to design a group of new bifunctional tTF fusion proteins to target procoagulatory activity selectively into the tumor vasculature and to induce tumor infarction [ 48 , 51 , 63 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Re-targeting Tf To Tumors—non-clinical Results and Translation Into The Clinicmentioning
confidence: 99%
“…tTF-NGR retained the procoagulatory activity of TF in a FX/FXa assay [ 69 , 70 , 71 ] and it revealed specific binding to the respective target molecules (CD13) on stimulated endothelial cells in vitro [ 70 , 71 , 72 ] and to tumor endothelium in vivo [ 65 ]. Multiple imaging techniques showed in vivo accumulation of tTF-NGR in tumor tissues and its in vivo-induced activation of coagulation with subsequent tumor vascular occlusion and inhibition of tumor vessel blood flow upon systemic application [ 67 , 68 , 69 , 70 , 71 , 72 , 75 , 80 ]. In contrast, these central activities were not observed when using tTF without a targeting moiety.…”
Section: Re-targeting Tf To Tumors—non-clinical Results and Translation Into The Clinicmentioning
confidence: 99%
“…In the same model, Huang et al later demonstrated induction of significant intravascular thrombosis and tumor necrosis, tumor growth inhibition, and increased survival using a construct with three RGD repeats fused to tTF [75]. Multiple other studies have investigated the efficacy of RGD and NGR-targeted coaguligands, primarily fused to the C-terminal region of tTF, with pre-clinical testing performed in human breast cancer (SKBR3 and MDA-MB-435), lung adenocarcinoma (A549 and MAD109), human fibrosarcoma (HT1080), glioblastoma (U87), melanoma (M21), small cell lung cancer (HTB119), and colorectal (CT26) cancer models (Table S1) [14,[76][77][78][79][80][81][82][83]. A study by Hallahan et al used embolic nanoparticles rather than tTF to target integrin α2bβ3 on radiation-primed tumor vessels [84].…”
Section: Integrins and Integrin Receptorsmentioning
confidence: 99%
“…Numerous molecules expressed exclusively at the surface of tumor endothelium have since been identified [12,13]. However, while the use of targeted agents increased selectivity, the issue of off-target toxicity related to the delivery of cytotoxic agents still remained [14,15].…”
Section: Introduction-the Origins Of Vascular Targeting For Precision Thrombosismentioning
confidence: 99%
“…Kessler, et al has proven that the fusion of integrin α5β1 with tTF could induce embolization of the tumor blood vessel in adenocarcinoma, melanoma and fibrosarcoma, thereby suppressing the tumor growth [13]. The tTF-NGR designed by Christian, et al reduced the growth of fibrosarcoma transplanted tumors [14]. As an effector molecule targeting tumor vascular embolism, we need to explore tTF-related targeted drugs for colon cancer treatment.…”
mentioning
confidence: 99%